Effect of hysteroscopic septum resection on IVF/ICSI outcomes in women with septate uterus: a propensity-score retrospective matching study - Wei Zhang; Shunzhi He; Xiaoyan Zhang; Zhenteng Liu; Min Chu; Xuemei Liu; Hongchu Bao (Reproductive Biology and Endocrinology)
Abstract Background Hysteroscopic septum resection has been a widespread technique throughout the world in women with a septate uterus. The effectiveness of hysteroscopic septum resection before IVF was equivocal. This study aimed to investigate whether hysteroscopic septum resection could improve IVF outcomes for women with a septate uterus. Methods This retrospective case-control study was carried out from January 2017 to December 2022. We included subfertile women with septate uterus (n = 147), including 113 women undergoing hysteroscopic septum resection and 34 women opting for expectant management before IVF/ICSI. In addition, we selected 147 women with normal uteri using propensity score matching (PSM). The clinical outcomes of IVF/ICSI were compared by logistic regression and Cox proportional regression in each group. Results During follow-up time, clinical pregnancy occurred in 66 women who underwent hysteroscopic septum resection (58.41%), compared to 23 women opting for expectant management (67.65%, OR 1.783, 95% CI 0.725–4.380) and 87 women with normal uteri (59.18%, OR 2.601, 95% CI 1.202–5.631). Miscarriage occurred in 12 women who underwent hysteroscopic septum resection (18.18%) versus 5 women who had expectant management (21.74%, OR 1.098, 95% CI 0.323–3.734) and 8 women with normal uteri (9.20%, OR 0.278, 95% CI 0.078–0.997), while preterm birth occurred in 7 women who underwent hysteroscopic septum resection (10.61%) versus 1 women who had expectant management (4.35%, OR 0.509, 95% CI 0.056–4.666) and 9 women with normal uteri (10.34%, OR 1.472, 95% CI 0.291–7.447). Live birth occurred in 54 women following hysteroscopic septum resection (47.79%) compared to 18 women following expectant management (52.94%, OR 1.368, 95% CI 0.589–3.175) and 78 women with normal uteri (53.06%, OR 1.641, 95% CI 0.941–2.864). Conclusions Women who underwent hysteroscopic septum resection had lower clinical pregnancy rate and higher risk of miscarriage compared to those with normal uteri, but there was no significant difference in live birth rate between the groups. Trial registration This is a retrospective case-control study.